Analysis of feed fish processing business in district district Siak Hulu Kampar - Huria, Candra; Chalid, Nursiah; Sari, Lapeti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The presence of fish feed businesses in the District of Kampar regencySiak Hulu has a contribution in supporting regional economicdevelopment. Fish food processing industry has not experienced growth in terms of numbers, but in terms of the advancement of knowledge in the modern age as it makes the Siak Hulu district more and more interested in trying to establish fish feed businesses. Opportunities in the domestic market for this commodity is still very open,because of the consumption of fodder for livestock entrepreneurs so that the demand for animal feed is relatively stable and even tended to increase.The research was conducted on the Siak Hulu district Kampar regency.Formulation of the problem in this study is whether the fish food processing business in the District of Kampar regency Siak Hulu could be developed in termsof its economy. The purpose of this study was to determine the development of fish feed processing business in the District of Kampar regency Siak Hulu. Population and samples in this study were all fish feed processing industry owned by the people in the District Siak Hulu, amounting to 9 business units.Based on the results of analysis show that the average amount of revenuefish food processing business in the District of Kampar regency Siak Hulu is Rp.3016667 with a total production cost of Rp. So the revenue of Rp 2,035,824.94.980,841.72. BEP value of production volume in Siak Hulu district of 230 kg or Rp. 1,150,000.00 per month.Keywords : Feed Fish Processing.